Spatial distribution and evolution of fault-segment boundary types in rift systems; observations from experimental clay models - Whipp,PS; Jackson,CA-L; Schlische,RW; Withjack,MO; Gawthorpe,RL (2015)
Fault-segment boundaries initiate, evolve and die as a result of the propagation, interaction and linkage of normal faults during crustal extension. In this study we use a series of scaled physical models (wet clay) to investigate the distribution and evolution of fault-segment boundaries within an evolving normal fault population during orthogonal extension. From the models we can establish a simple geometric classification for segment-boundaries, analyse their spatial and temporal evolution and identify key factors that influence their variability. Development of overlapping fault tips is a pre-requisite for fault growth via segment linkage. Synthetic segment boundaries are the most common segment-boundary type developed in the models. The proportion of synthetic segment boundaries in the total fault population increases with increased strain, whereas conjugate (antithetic) segment boundaries are very rare. Hangingwall-breached relay ramps are the most common type (>70%) of breached segment-boundary, followed by footwall-breached relay ramps (<25%). Transfer faults are uncommon in our models. The fault overlap to fault spacing aspect ratio of a synthetic segment-boundary does not allow for predictions of the type of breached segment-boundary that will develop. Fault linkage occurs in a range of styles across a wide range of fault overlap-spacing ratios (1:1 to 7:1).Volume EditorAssigned